Enriching The Vocabulary of The Eighth Graders Of SMPN 38 Palembang by Using Action Race Game - Esti Rohida,; Jaya Nur Iman,; Nike Angraini, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Vocabulary is an important aspect of language learning. Vocabulary is important to learn because it can help students understand listening and learning materials and create good sentences in speaking and writing. It can be challenging for students’ to memorize English words, therefore they still need to increase their vocabulary achievement in order to become proficient in the language. Therefore, the writer investigted the used of Action Race Game to find out whether or not there was any significant enrichment on students’ vocabulary after the instrument applied and whether or not there was any significant mean difference between those who were taught by using action race game and those who were not. The research used the experimental group and control group consisted 67 students’ eighth class SMPN 38 Palembang. To asses students’ vocabulary achievement, the writer proceeded the pre-test at the beginning of the research and followed the post-test end of research. The vocabulary achievement was analyzed by using SPSS. The result of this study indicated that there was there any significant difference between those who were taught by using action race game and those who were not. It was found that t-obtained value was 13.552 at significant value of p<0.005, the t-table value was 2.0369. Since t-table value of t-obtained is higher that t- table, the null hypothesis (Ho) was rejected and the null hypothesis (H1) was accepted. In other words, the use of action race game in vocabulary learning had positive effects on their vocabulary learning.